(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
Based on the pioneering work of M.ª Lourdes Albertos and the subsequent bibliography, we propose here some reflections on the relationship between local theonymy, human groups and toponyms in the Hispanic West, reviewing the characteristics of the epithets of the theonymic forms. The conclusion is that, despite evidence of this link, theonymic forms are ambiguous and lack parallels to establish more far-reaching conclusions.